Magicalamity - Saunders, Kate, 1960- (Delacorte Press, 2012)
Eleven-year-old Tom is shocked to learn that he is a demisprite, half fairy and half mortal, and that he, aided by three fairy godmothers, must save his father, who is hiding in the fairy Realm, while safeguarding his mortal mother.